Highly responsive NaCl detector based on inline microfiber Mach–Zehnder interferometer - Jaddoa, M.F.; Jasim, Ali Abdulhadi; Razak, M.Z.A.; Harun, Sulaiman Wadi; Ahmad, Harith (Elsevier, 2016)
This paper details the fabrication and performance evaluation of a sodium chloride (NaCl) detector based on an inline microfiber Mach–Zehnder interferometer (IMMZI) that had been fabricated via a glass fiber processing system (Vytran GPX-3400). Spectral characteristics of IMMZIs possessing a variety of waist diameters and situated within assorted concentrations of NaCl solutions are also reported. An optimally high responsitivity to NaCl solutions of about 2913.7 nm per refractive-index unit (RIU) was exhibited by an IMMZI with a total length of 34 mm and a tapered waist diameter of 10 μm, in which the RI ranged from 1.31837 to 1.31928.